EFFECT OF THE HELIUM-NEON LASER ON THE HEALING OF EXTRACTION WOUNDS - A HISTOLOGICAL STUDY IN RATS - Niccolifilho, W.; Okamoto, T. (Laser Inst Amer, 1994)
A histological study on the healing of extraction wounds following laser irradiation using a He-Ne laser, was carried out in rats. The results suggest that this mode of treatment has a beneficial effect on initial bony wound healing. Proliferation of fibroblasts and formation of trabecular osteoid tissue were found to be more prominent within the irradiated group. The deposition of led in the newly formed bone suggests swifter ossification within the irradiated group.
Keywords: BIOESTIMULATION; LOW-ENERGY; HE-NE LASER; DENTAL EXTRACTION WOUND; WOUND HEALING